Different maturation of gut microbiome in Korean children - Kim, Jieun; Kim, Erin; Kim, Bongyoung; Kim, Jinsup; Lee, Hyun Ju; Park, Jun-Sun; Hwang, Sehee; Rho, Mina; Pai, Hyunjoo (Frontiers in Microbiology, 2022)
Gut microbiome plays a crucial role in maintaining human health and is influenced by food intake, age, and other factors. In this study based in Korea, we examined the bacterial taxonomic composition of the gut microbiota in infants (≤ 1 year), toddlers (1–<4 years), and school-aged children (4–13 years) and compared them with those of healthy adults to investigate the microbiota changes in early life and their association with the resistome. We used whole metagenome sequences obtained by Illumina HiSeq sequencing and clinical information of 53 healthy children, and sequence data of 61 adults from our previous study. Our results indicate that the bacterial composition of the gut in the population ranging from infants to adults forms three clusters: the Ruminococcus-Eubacterium (G1), Bifidobacterium-Escherichia (G2), and Bacteroides-Faecalibacterium (G3) groups. The gut microbiota of infants and toddlers (100% of infants and 85% of toddlers) constituted mostly of G2 and G3 groups, whereas 90% of adults showed G1-type gut microbiota. School-aged children showed a transitional gut microbiota composition of both infants and adults (31%, 38%, and 31% in G1, G2, and G3, respectively). Notably, the three clusters of microbiota showed significantly different patterns of bacterial diversity (p < 0.001): G2 showed the lowest Shannon index, followed by G3 and G1 (1.41, 2.08, and 2.48, respectively; median Shannon index). When combined with the adult group, alpha diversity showed a positive correlation with age (R2 = 0.3). Furthermore, clustering the composition of antibiotic resistance genes (ARG) identified two clusters (A1 and A2), and most of G1 (95%) and G3 (80%) belonged to A1. However, G2 showed the least diversity and the highest abundance of ARGs. Nine ARG families showed a significant difference among age groups; three tetracycline resistance genes, tet32, tetO, and tetW, showed a positive correlation, and six other genes, ampC, TEM, ileS, bacA, pmr transferase, and cepA, showed a negative correlation with age. In conclusion, our results highlighted that a delayed persistence of the Bifidobacterium-dominant enterotype with a lower bacterial diversity was observed in Korean children up to 13 years of age, which suggests a different maturation process with a delayed maturation time.